LOGISTICS IN AGRIBUSINESS´ ACTIVITY IN UKRAINE - Smyrnov, Ihor; Shmatok, Oksana (Human Geography Journal, 2015)
Agrologistics is one of the industries most dynamic in Western Europe. In Ukraine, agrologistics, in contrast to the overall and transport logistics, is in the initial stage of its development, but it is a very promising direction. Logistics are extremely effective, particularly in the case of agricultural holdings or large vertically integrated corporate structures in agribusiness. In Ukraine these are the «Nibulon», «Mironivskyy Hliboproduct», «Terra food», etc., as well as companies with foreign capital – AMACO, «Agro-Maas NV», «Kernel-Trade» and others. Development of agrologistics will help to bring the country's agriculture to a new, world level of its development and efficiency.